Impacto de los costos logísticos en la competitividad de las cadenas de suministro agroexportadoras peruanas en el contexto del TLC Perú-EE. UU. al 2015 - Schwarz Díaz, Max (2016)
This research develops an analysis of the impact of logistics costs on the competitiveness of the extended supply chains of Peruvian agro-exporting companies that operate in the context of the Free Trade Agreement (FTA) between the United States and Peru. To do so, it correlates the costs distribution behavior of seven supply chains: the exports of asparagus, coffee, mango, grapes, cacao, quinoa, and onion, which operate under the FTA, with the results of the Compared Revealed Exports Advantage Index (IVCRE) applied to each of the agro-industrial supply chains studied.